SAT for dummies : a Wiley Brand - Woods, Geraldine; Wolfdolff, Ron (For dummies, 2015)
The easy way to prepare for the SAT The College Board has announced a redesign to the SAT in the spring of 2016. There's no doubt that students, parents, and educators are clamoring for a revised and authoritative resource on the latest iteration of this important standardized test.